(untitled) (Journal of Academic Research, 2026)
Short abstract. This study aimed to examine the relationship between burnout and family adjustment among kindergarten teachers in the city of Misurata, with attention to possible differences between married and unmarried teachers. The descriptive correlational method was used, and the sample consisted of 80 teachers, distributed between married and unmarried participants. The Maslach Burnout Inventory and the Family Adjustment Scale developed by Mohamed Abdel Hamid were applied, after verifying their reliability and validity. Data were analyzed using the SPSS program, employing several statistical methods such as the mean, standard deviation, frequency, percentages, in addition to the T-test and the Mann-Whitney test. The results revealed a statistically significant negative relationship between burnout and family adjustment. The findings also indicated that kindergarten teachers, whether married or unmarried, reported a low level of burnout and a high level of family adjustment. No statistically significant differences were found in the variables based on marital status.